Prevalencia de síndrome metabólico en el personal docente del área biológica de la Universidad Técnica Particular de Loja, sede Loja, año 2017 - Jaramillo Bermeo, Daniel Alejandro (2018)
Abstract:Metabolic syndrome (MS) includes cardiometabolic risk factors such as abdominal obesity, dyslipidemia, elevated blood glucose and high blood pressure; for that reason, it is essential to establish its prevalence for the development of programs and timely strategies that emphasize the modification of lifestyles. Objective: establish the prevalence of metabolic syndrome in the teaching staff of the Biological Area that works at the Universidad Técnica Particular de Loja, during 2017. Methods: A cross - sectional study was carried out in 92 teachers from the Biological Area of the UTPL using the diagnostic criteria of MS established by the ATP III with the modification of the AHA / NHLBI of 2005. Results: prevalence of metabolic syndrome was found to be 8.69% (more frequently in males: 5.43%; while female 3.26%) with the highest prevalence at 54-59 years (3.26%). The most altered parameter was triglyceride levels (40.22%), predominantly in the male sex (48.94%). Conclusions: the SM constitutes a serious health problem in a good percentage of the teachers of the UTPL, a situation that warrants instituting mechanisms for the control of identified cases.